If it's not what You are looking for type in the equation solver your own equation and let us solve it.
27=y+15
We move all terms to the left:
27-(y+15)=0
We get rid of parentheses
-y-15+27=0
We add all the numbers together, and all the variables
-1y+12=0
We move all terms containing y to the left, all other terms to the right
-y=-12
y=-12/-1
y=+12
| d+47/5=-1 | | 9x-22+61+34+5x-7=360 | | 9=t-16 | | 21n-36=72-24n+44n | | -2k+30=-42 | | 2n^2+3n=-54 | | 3.1p+3.4=19.83 | | 24x-4=92 | | f/5+28=35 | | 24x-4=24 | | 7+4j=79 | | x/4-28=-2 | | 5(f-85)=60 | | 18=2w+14 | | (-2.1/7)p=-3 | | 2j+15=79 | | h/5-13=-9 | | 4/12=(x-3)/x | | g/2-7=3 | | 3^4/3^x=27 | | 7=-7x+10 | | 2*2^3=2^x | | r-49/10=4 | | 5-x2=1 | | r+20/9=5 | | 7y+5=123 | | 21+7f=98 | | 2+8y=58 | | 6p-3=p+17 | | 12/4=x/(x-3) | | 10(z-97)=30 | | 6x-16=2/3(3x+12 |